Structure, tritium depth profile and desorption from 'plasma-facing' beryllium materials of ITER-Like-Wall at JET. (August 2017) - Pajuste, E.; Kizane, G.; Vitins, A.; Igaune, I.; Avotina, L.; Zarins, R.; ,
Highlights: In ILW limiter beryllium tiles more than 95% of tritium is accumulated in the first 30–45 m from the 'plasma-facing' surface, however, possible presence of tritium in low concentration up to the depth of 100 m cannot be excluded. Highest tritium concentration can be found in the outer wall region of the vacuum vessel. The degree of detritiation of samples from beryllium tiles > 91% can be obtained upon reaching 1075 K. Erosion and melting of the beryllium can be observed in the central parts of the tiles, whereas side parts are mostly covered by the deposition layers. Abstract: Tritium depth profile and its temperature programmed desorption rate were determined for selected samples cut out of beryllium tiles removed from the Joint European Torus vacuum vessel during the 2012 shut down. A beryllium dissolution method under controlled conditions was used to determine the tritium depth profile in the samples, whereas temperature programmed desorption experiments were performed to assess tritium release pattern. Released tritium was measured using a proportional gas flow detector. Prior to desorption and dissolution experiments, the plasma-facing surfaces of the samples were studied by scanning electron microscopy and energy dispersive X-ray spectroscopy. Experimental results revealed that > 95% of the tritium was localized in the top 30 – 45 µm of the 'plasma-facing' surface, however, possible tritium presence up to 100 µm cannot be excluded. During temperature programmed desorption at 4.8 K/min in the flow of purge gas He + 0.1% H2 the tritium release started below 475 K, the most intense release occurred at 725 – 915 K and the degree of detritiation of > 91% can be obtained upon reaching 1075 K. The total tritium activity in the samples was in range of 2 – 32 kilo Becquerel per square centimetre of the plasma-facing surface area.